2013
DOI: 10.1016/j.jnucmat.2013.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grain size on radiation effects in a low carbon steel

Abstract: Ultra-fine grain (UFG) metals with a relatively large volume of interfaces are expected to be more radiation resistant than conventional metals; grain boundaries act as unsaturable sinks for neutron irradiation induced defects. Effects of neutron irradiation on conventional and ultra-fine grain structured carbon steel are studied using the PULSTAR reactor at NC State University to relatively low fluence ($1.15 Â 10 À3 dpa). The low dose irradiation of ultrafine grained carbon steel revealed minute radiation ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Interfaces in materials such as grain boundaries (GBs) can serve as sinks for absorbing and annihilating radiation-induced defects [11,12]. Many experiments have demonstrated that nano-structured metals have enhanced radiation tolerance compared to their bulk counterparts, such as nano-crystals [11,13,14,15,16], nano-layers [17] and so on. Computer modeling has been commonly used to investigate defect production and annealing near interfaces [12,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Interfaces in materials such as grain boundaries (GBs) can serve as sinks for absorbing and annihilating radiation-induced defects [11,12]. Many experiments have demonstrated that nano-structured metals have enhanced radiation tolerance compared to their bulk counterparts, such as nano-crystals [11,13,14,15,16], nano-layers [17] and so on. Computer modeling has been commonly used to investigate defect production and annealing near interfaces [12,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Next to the particles, also the grain size distribution in the matrix plays an important role for the performance of the material . In addition, the usual influence on mechanical properties, grain boundaries also increase the radiation resistance . In practice, a lack in reproducibility of the mechanical properties of these steels caused by an insufficient ability to control the microstructure evolution during the fabrication process has been a serious shortcoming .…”
Section: Introductionmentioning
confidence: 99%
“…However, the data on the effect of high-dose neutron irradiation on stability of commercial nanostructured materials in the environment of real reactors are poorly presented in the literature. The first publications in this area were focused on the 321 stainless steel produced by ECAP [219] and low-carbon steel produced by ECAP-C [220,221]. In [219], a study of ECAP 321 steel before and after the neutron irradiation at temperature *350°C in the reactor BOR-60 with the maximum damage dose 5.3 dpa was carried out.…”
Section: Irradiation Resistance Of Bulk Nanostructured Metallic Matermentioning
confidence: 99%
“…However, the steel after ECAP was characterized by a rather wide distribution of grain sizes and substructures, so a conclusion of further studies to clarify and explain the observed regularities was drawn. Studies in [220,221] focused on steel 10 produced by ECAP-C, which was subjected to neutron irradiation with the maximum dose of 1.37 dpa. High number densities of nano-Mn-Si-enriched precipitates were observed in both coarse-grained and UFG steels after irradiation (Fig.…”
Section: Irradiation Resistance Of Bulk Nanostructured Metallic Matermentioning
confidence: 99%